Effect of Hurricane Irma on daily direct‐care nurse staffing in nursing homes. Issue 8 (12th May 2021) - Jester, Dylan J.; Thomas, Kali S.; Peterson, Lindsay J.; Dosa, David M.; Andel, Ross; Hyer, Kathryn
Abstract: Objectives: To examine the effect of Hurricane Irma on staff‐related financial expenditures and daily direct‐care nurse staffing levels. Design: Retrospective cohort study. Setting: September 3–24, 2017 in the state of Florida, United States. Hurricane Irma made landfall on September 10, 2017. Participants: Six hundred and fifty‐three nursing homes (NHs), 81 evacuated facilities, and 572 facilities that sheltered‐in‐place. Measurements: This study used data from Payroll‐Based Journaling (PBJ), Certification and Survey Provider Enhanced Reports (CASPER), and Florida's health providers' emergency reporting system. PBJ provided estimates of daily direct‐care nurse staffing levels for registered nurses, licensed practical nurses, and certified nursing assistants. CASPER reported facility‐level characteristics such as profit status, chain membership, and special care unit availability. Florida's emergency reporting system identified evacuation status during Hurricane Irma. Linear mixed‐effects models were used to estimate the unique contribution of evacuation status on daily staffing increases over time from September 3 to 10. Results: Among all facilities, we found significant increases in staffing for licensed practical nurses ( p  = 0.02) and certified nursing assistants ( p  < 0.001), but not for registered nurses ( p  = 0.10) before Hurricane Irma made landfall. From 1 week before landfall to 2 weeks after landfall (September 3–24), an additional estimated $2.41 million was spent on direct‐care nurse staffing. In comparison to facilities that sheltered‐in‐place, evacuated facilities increased staffing levels of all nurse types (all p  < 0.001). At landfall, evacuated facilities spent an estimated $93.74 on nurse staffing per resident whereas facilities that sheltered‐in‐place spent $76.10 on nurse staffing per resident. Conclusion: NHs face unprecedented challenges during hurricanes, including maintaining adequate direct‐care nurse staffing levels to meet the needs of their residents. NHs that evacuated residents had an increase in direct‐care nurse staffing that was greater than that seen in NHs that sheltered‐in‐place.